A comparative study of quality of life among elderly people living in old age homes and in the community - Kengnal, Prakash R.; Bullappa, Asha; M. S., Ashok Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: The ageing process is not determined truly by genes and personal characteristics but mainly by his adjustment with the environment he lives. Ageing of a person depends on many factors which influence the course of life like physiological, social, psychological, economic, environmental and cultural factors which in turn affect the quality of life (QoL). Given these findings, quality of life is influenced by the place where a person lives. The objective of the study was to assess and compare the quality of life of elderly living in old age homes and community. Methods: This was a cross sectional, questionnaire based study done on elderly people (>60 years) living in old age home, urban and rural area. The study was carried out for a period of 3 months from April to June 2016 after taking consent from the study participants. WHOQoL-BREF questionnaire was used to assess the quality of life. Results: Elderly females were more than elderly males in rural and old age home. The study participants of all the three places were concentrated in the age group 65-70 years old. The mean scores of physical, psychological and social domains were high in urban elderly people. Most of the study population was illiterate in urban and rural area but in old age home most of them were educated. There was significant difference between the mean scores for psychological and environmental domain (p=0.048 and 0.001 respectively). Conclusions: Participants living in the urban area had higher mean scores in the physical, psychological and social domains as compared to rural area and old age home. The mean score of environmental domain was high in rural area as compared to urban and old age home.